206k views
4 votes
8) g = xc + y, for x

User Tylerargo
by
5.4k points

2 Answers

7 votes

if you are solving for X,

subtract y from both sides = g - y = xc

divide by c = g - y / c = x

User Khepri
by
5.1k points
4 votes

Answer:

x = (g - y)/c

Explanation:

You are solving for x. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS. PEMDAS =

Parenthesis

Exponent (& Roots)

Multiplication

Division

Addition

Subtraction

First, subtract y from both sides:

g = xc + y

g (-y) = xc + y (-y)

g - y = xc

solate the variable, x. Divide c from both sides:

(g - y)/c = (xc)/c

(g - y)/c = x

x = (g - y)/c is your answer.

~

User Mus
by
5.0k points